Statement of Testimony: Commission on Safety and Abuse in America's Prisons - Jack Cowley (Washington University Journal of Law & Policy, 2006)
I believe that we have for too long considered prisons as places to promote public safety by means of the incapacitation of offenders rather than places that promote public safety by releasing offenders who are less likely to reoffend. It is widely accepted that, nationally, approximately 67.5% of released offenders are arrested within three years of their release. It is my professional opinion, gained from my many years as a prison warden and continued work in the field, that this figure is higher than it needs to be; prisons, when used as tools of crime reduction, can be effective.
Keywords: Prison administration; Prisoner abuse; Prisons; United States